1992
DOI: 10.1002/hep.1840150207
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of bile duct stones by extracorporeal shock-wave lithotripsy: A five-year experience

Abstract: Over 5 yr, 103 elderly patients (mean age = 70 yr) with bile duct stones (mainly not amenable to endoscopic extraction) underwent adjuvant extracorporeal shock-wave lithotripsy using a first-generation kidney lithotripter. Disintegration of stones was achieved after a mean of 1.4 sessions in 92% of the patients. Spontaneous passage of fragments into the duodenum occurred in one fourth of the patients, and endoscopic extraction of fragments was necessary in 75% of the patients, resulting in complete clearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 37 publications
1
17
0
5
Order By: Relevance
“…It was first used to treat bile duct stones in 1985, after its success and safety in treating renal calculi had been well established (9,10). Sauerbruch et al (9) demonstrated the efficacy of ESWL in achieving Common Bile Duct, stone disintegration in more than 90% of patients with minimal side effects. Okada et al (4) reported excellent results using this method for intrahepatic bile duct stone after choledochal cyst resection, and to the best of our knowledge, this was the first report showing the effectiveness of ESWL on biliary stones after choledochal cyst surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It was first used to treat bile duct stones in 1985, after its success and safety in treating renal calculi had been well established (9,10). Sauerbruch et al (9) demonstrated the efficacy of ESWL in achieving Common Bile Duct, stone disintegration in more than 90% of patients with minimal side effects. Okada et al (4) reported excellent results using this method for intrahepatic bile duct stone after choledochal cyst resection, and to the best of our knowledge, this was the first report showing the effectiveness of ESWL on biliary stones after choledochal cyst surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ist die Extraktion eines großen Konkrementes nach Papillotomie nicht mög-lich, kann bei zusätzlichem Einsatz verschiedener Lithotripsiemethoden (spezielle Lithotripterkörbchen,intrakorporale elektrohydraulische oder Laserlithotripsie, extrakorporale Stoßwellenlithotrip-sie) eine Sanierung der Gallengänge in 95% der Fälle erreicht werden [86,87,88] scher (oder offener) Cholezystektomie ("therapeutisches Splitting") das favorisierte Verfahren [89].…”
Section: Therapie Der Symptomatischen Choledocholithiasis Und Cholangunclassified
“…ein weiteres Lithotripsieverfahren eingesetzt werden. Die perkutane extrakorporale Stoßwellenlithotripsie (ESWL) wird seit Mitte der 80er Jahre zur Behandlung der therapierefraktären Choledocholithiasis angewendet [24][25][26]. Sie ermöglicht ohne direkten Steinkontakt unter radiologischer oder sonographischer Ortung Behandlungen mit gutem Desintegrationsergebnis.…”
Section: Endoskopische Retrograde Technikenunclassified